The organization of classes by physical education of students of higher educational institutions taking into account their interests and individual physical development - Natalia Novitskaya (Kharkiv State Academy of Physical Culture, 2015)
Purpose: the definition of criteria of an assessment of specific features of physical development and adequate to it norms of the motive activity. Material and Methods: the analytical synthesis of data of literature, clinical anthropometry of the investigated contingent, the use of sign semantic spaces, methods of an assessment of a biological age. Results: the nature of creation of standards is considered for a control of the level of physical development and an assessment of physical fitness of students. Conclusions: the organization of classes by physical training in HEI has to be based on the accounting of individual physical development, the available level of physical fitness and the current physical state